Regulatory support of calculation of dimensional chains in assembling with thermal influence - Черкашина, Ольга Сергіївна (Technology audit and production reserves, 2013)
The article deals with regulatory support of assembling accuracy with thermal influence of multi-element junctions due to the calculation of dimensional accuracy at the stage of technological preparation of production with regard to temperature gaps formed during heating and assembling of product elements. The analysis of processes that take place under the influence of temperature in the contact zone of mounting surface of parts of multi-element junctions was conducted in the paper, as well as mathematical modeling of the thermal state of the product was carried out and the regularities of the temperature gap change were determined through the use of existing systems of computer-aided engineering analysis. Based on the analysis, an improved formula for calculating the dimensional accuracy of the assembly was obtained and classification of the «bush» type parts with models of determining the temperature gaps, which are included in this calculation, was proposed.